Ultra‐high‐field magnetic resonance spectroscopy in non‐alcoholic fatty liver disease: Novel mechanistic and diagnostic insights of energy metabolism in non‐alcoholic steatohepatitis and advanced fibrosis. (20th May 2017) - Traussnigg, Stefan; Kienbacher, Christian; Gajdošík, Martin; Valkovič, Ladislav; Halilbasic, Emina; Stift, Judith; Rechling, Christian; Hofer, Harald; Steindl‐Munda, Petra; Ferenci, Peter; Wrba, Fritz; Trattnig, Siegfried; et al.
Abstract: Background & Aims: With the rising prevalence of non‐alcoholic fatty liver disease (NAFLD) and steatohepatitis (NASH) non‐invasive tools obtaining pathomechanistic insights to improve risk stratification are urgently needed. We therefore explored high‐ and ultra‐high‐field magnetic resonance spectroscopy (MRS) to obtain novel mechanistic and diagnostic insights into alterations of hepatic lipid, cell membrane and energy metabolism across the spectrum of NAFLD. Methods: MRS and liver biopsy were performed in 30 NAFLD patients with NAFL (n=8) or NASH (n=22). Hepatic lipid content and composition were measured using 3‐Tesla proton ( 1 H)‐MRS. 7‐Tesla phosphorus ( 31 P)‐MRS was applied to determine phosphomonoester (PME) including phosphoethanolamine (PE), phosphodiester (PDE) including glycerophosphocholine (GPC), phosphocreatine (PCr), nicotinamide adenine dinucleotide phosphate (NADPH), inorganic phosphate (Pi), γ‐ATP and total phosphorus (TP). Saturation transfer technique was used to quantify hepatic ATP flux. Results: Hepatic steatosis in 1 H‐MRS highly correlated with histology ( P <.001) showing higher values in NASH than NAFL ( P <.001) without differences in saturated or unsaturated fatty acid indices. PE/TP ratio increased with advanced fibrosis (F3/4) ( P =.002) whereas GPC/PME+PDE decreased ( P =.05) compared to no/mild fibrosis (F0‐2). γ‐ATP/TP was lower in advanced fibrosis ( P =.049), while PCr/TP increased ( P =.01). NADPH/TP increased with higher grades of ballooning ( P =.02). Pi‐to‐ATP exchange rate constant ( P =.003) and ATP flux ( P =.001) were lower in NASH than NAFL. Conclusions: Ultra‐high‐field MRS, especially saturation transfer technique uncovers changes in energy metabolism including dynamic ATP flux in inflammation and fibrosis in NASH. Non‐invasive profiling by MRS appears feasible and may assist further mechanistic and therapeutic studies in NAFLD/NASH.